Specifying mobile network using a wp-like formal approach - Kumar Singh, Awadhesh; Ghanekar, Umesh; Bandyopadhyay, Anup Kumar (Revista Colombiana de Computación, 2005)
The paper aims at providing a formal system, motivated by Dijkstra’s weakest precondition logic, for specifying mobile network. The paper shows how mobility can be specified using a state and transition based approach, which allows mobile hosts to be treated as nodes in a traditional statically structured distributed system. Another goal is to reason formally about the possible behaviors of a system consisting of mobile components. The handover procedure serves as an illustration for the notation. The contribution of the paper is the development of a style of modeling and reasoning about the temporal properties that allows for a straightforward and thorough analysis of mobile systems. Keywords: weakest precondition, mobile computing, specification, verification, safety, handover.